On finite element uniqueness studies for Coulomb's frictional contact model - Hild, Patrick (Zielona Góra: Uniwersytet Zielonogórski)
We are interested in the finite element approximation of Coulomb's frictional unilateral contact problem in linear elasticity.
Keywords: Coulomb's friction law; finite elements; mesh-size dependent uniqueness conditions; non-uniqueness example